1961
DOI: 10.1901/jeab.1961.4-133
|View full text |Cite
|
Sign up to set email alerts
|

Resistance‐to‐extinction Functions in the Single Organism

Abstract: Functions relating the number of reinforcements to some aspect of behavior are most often obtained through the use of different groups of subjects, each given different numbers of reinforcements before a test phase that is the same for all groups. The average of the individual measurements in each group then is related to the number of reinforcements given each group. By such a method, the classic data of Williams (1938) and Perin (1942) have shown that both the mean number of extinction responses and the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1

Year Published

1962
1962
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
0
26
1
Order By: Relevance
“…Several studies have demonstrated a positive relation between resistance to extinction and the number of reinforcers delivered during training (e.g., Hearst, 1961). In other words, the greater the reinforcement history, the greater the amount of resistance to change (i.e., to extinction).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a positive relation between resistance to extinction and the number of reinforcers delivered during training (e.g., Hearst, 1961). In other words, the greater the reinforcement history, the greater the amount of resistance to change (i.e., to extinction).…”
Section: Discussionmentioning
confidence: 99%
“…The PREE has been demonstrated using a variety of subjects, responses, and reinforcers, as well as with both free-operant and discrete-trial procedures, although almost always with between-subject designs. By contrast, many attempts to replicate the effect using within-subject designs have failed (e.g., Adams, Nemeth, & Pavlik, 1982;; but see Hearst, 1961, for a notable exception).…”
Section: Basic (Nonclinical) Researchmentioning
confidence: 99%
“…They had already been trained to peck a key for grain reinforcement in a previous experiment (Hearst, 1961 APRIL, 1962 correct key (the last-rewarded key) continued to produce 2-sec blackouts; no reinforcement was possible until the subject switched to the other key. A correct response produced a 1-sec grain reinforcement followed by a 2-sec blackout.…”
Section: Subjectsmentioning
confidence: 99%